2015
DOI: 10.1103/physrevb.91.245114
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the band gap problem on oxidation and hydration in acceptor-doped barium zirconate

Abstract: Charge carrier concentrations in acceptor-doped proton-conducting perovskites are to a large extent determined by the hydration and oxidation of oxygen vacancies, which introduce protons and holes, respectively. First-principles modeling of these reactions involves calculation of formation energies of charged defects, which requires an accurate description of the band gap and the position of the band edges. Since density-functional theory (DFT) with local and semi-local exchangecorrelation functionals (LDA and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 89 publications
(112 reference statements)
7
35
0
Order By: Relevance
“…46 It should be mentioned that the so-called over binding problem (oxygen energy see third section of this work) by the RPBE exchange-correlation functional as well as the underestimation of the band gap by this procedure might be overcome using the Heyd-Scuseria-Ernzerhof (HSE) functional [47][48][49] as well as other sophisticated approaches. 50 However, this would increase the computational costs and was therefore not considered in this work.…”
Section: Chemical Stability Of Bzomentioning
confidence: 99%
“…46 It should be mentioned that the so-called over binding problem (oxygen energy see third section of this work) by the RPBE exchange-correlation functional as well as the underestimation of the band gap by this procedure might be overcome using the Heyd-Scuseria-Ernzerhof (HSE) functional [47][48][49] as well as other sophisticated approaches. 50 However, this would increase the computational costs and was therefore not considered in this work.…”
Section: Chemical Stability Of Bzomentioning
confidence: 99%
“…Theoretically, previous studies have revealed that advanced electronic structure calculations are needed to correctly describe this oxidation phenomenon. Indeed, the generalized gradient approximation (GGA) finds it exothermic in several perovskite oxides [10][11][12], while hybrid functionals (PBE0) provide an endothermic picture [12]. This is related to the band-gap problem, more precisely to the incorrect position of the valence band maximum, formed by oxygen-2p states, obtained with GGA.…”
Section: ••mentioning
confidence: 99%
“…Alternatively, the hole mobility could be dominated by the few holes thermally excited in the itinerant level [12].…”
Section: Hole Diffusion In the Latticementioning
confidence: 99%
“…[6][7][8][9] When fitted to the Arrhenius-like expression T σ h = Ae −Ea/kT (8) these conductivities (σ h ) yield activation energies (E a ) within the range of 0.6 eV to 1.1 eV. In previous work 24 we calculated the activation energy for the hole conductivity based on the endothermic oxidation reaction in Eq. (1) assuming that the hole mobility could be described by band conduction, i.e., B h ∼ T −1 .…”
Section: Hole Conductivitymentioning
confidence: 99%
“…It is well-known that DFT using local and semi-local XC functionals severely underestimates band gaps and this can affect the description of holes, which is sensitive arXiv:1603.06728v2 [cond-mat.mtrl-sci] 4 Jul 2016 to the position of the valence band maximum (VBM). In a previous paper 24 we went beyond the semi-local approximation and used DFT with hybrid functionals as well as many-body perturbation theory (G 0 W 0 ) in order to study how the description of the band gap affects the formation of band state holes. Along with a more accurate band gap we found the oxidation reaction [Eq.…”
Section: Introductionmentioning
confidence: 99%